2008
DOI: 10.1121/1.2832617
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intelligibility of ideal binary-masked speech: Implications for noise reduction

Abstract: The application of the ideal binary mask to an auditory mixture has been shown to yield substantial improvements in intelligibility. This mask is commonly applied to the time-frequency (T-F) representation of a mixture signal and eliminates portions of a signal below a signal-to-noise-ratio (SNR) threshold while allowing others to pass through intact. The factors influencing intelligibility of ideal binary-masked speech are not well understood and are examined in the present study. Specifically, the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
196
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(218 citation statements)
references
References 29 publications
15
196
2
5
Order By: Relevance
“…As with the algorithm, it was found that the IBM improved recognition of isolated phonemes, thus extending results observed previously for sentences (Anzalone et al, 2006;Brungart et al, 2006;Li and Loizou, 2008;Wang et al, 2008Wang et al, , 2009Cao et al, 2011;Sinex, 2013). This result should not be surprising, given the effectiveness of algorithm processing observed here and the fact that the algorithm aimed to estimate the IBM.…”
Section: Algorithm and Ibm Processingsupporting
confidence: 73%
See 3 more Smart Citations
“…As with the algorithm, it was found that the IBM improved recognition of isolated phonemes, thus extending results observed previously for sentences (Anzalone et al, 2006;Brungart et al, 2006;Li and Loizou, 2008;Wang et al, 2008Wang et al, , 2009Cao et al, 2011;Sinex, 2013). This result should not be surprising, given the effectiveness of algorithm processing observed here and the fact that the algorithm aimed to estimate the IBM.…”
Section: Algorithm and Ibm Processingsupporting
confidence: 73%
“…This difference is generally obscured when using sentence materials, as IBM scores tend to reach ceiling values (e.g., Brungart et al, 2006;Li and Loizou, 2008;Wang et al, 2009;Sinex, 2013). Another consequence is that the increased effectiveness of IBM processing for HI listeners is reflected with clarity when assessed as the distance between IBM scores and scores in quiet (see Fig.…”
Section: Assessing Benefitmentioning
confidence: 99%
See 2 more Smart Citations
“…Binary masking refers to algorithms that decompose the signal into T-F units and select those units satisfying a given criterion (e.g., SNR > 0 dB, for noise suppression), while discarding the rest by applying a binary mask to the units of the decomposed signal, i.e., the mask for a given T-F unit is set to 0 if it does not satisfy a given criterion or is set to 1 if it satisfies the criterion (Wang and Brown, 2006). Binary masks have been widely used for different speech enhancement as well as sound separation applications resulting in gains in intelligibility and quality of the processed noisy speech (Wang and Brown, 2006;Kim et al, 2009;Li and Loizou, 2008). Use of the binary masks for dereverberation, which was only evaluated by a few studies, is attractive as it does not rely on the inversion of the RIR.…”
Section: Introductionmentioning
confidence: 99%